Revised karyotype of Alouatta caraya (Primates: Platyrrhini) based on synaptonemal complex and banding analyses - Mudry, M.D. (1998)
Most primates studied have the usual XX/XY sex-chromosome system. However, exceptions to this rule among howler monkeys have been suggested by several authors. Recently a quadrivalent was discovered in male meiosis of Alouatta caraya and it was established that this species has an X1X2Y1Y2 sex chromosome system. On that basis, a cytogenetic analysis of 25 males of this species is described. showing the corrected karyotype of this species. Each chromosome involved in the particular sex-chromosome system of this species is identified on the basis of mitotic chromosome measurements. G and C-banding patterns as well as on the relative measurements of synaptonemal complexes. It is now established that A. caraya has a karyotype with 2n = 52 in both sexes, and that the male one shows a single autosome 7 (X2) besides the X (X1) and the two products of the reciprocal translocation between the second autosome #7 and the Y chromosome (Y1 and Y2), while females show a homomorphic pair #7 (X2) and a pair of X1. The evolutionary implications of the exceptional primate species having composite sex-chromosome systems are discussed.